Low values of central venous oxygen saturation (ScvO2) during surgery and anastomotic leak of abdominal trauma patients (2017)
Background: There is a well known relationship between hypoperfusion and postoperative complications like anastomotic leak. No studies have been done addressing this relationship in the context of abdominal trauma surgery. Central venous oxygen saturation is an important hypoperfusion marker of potential use in abdominal trauma surgery for identifying the risk of anastomotic leak development. The purpose of this study was to identify the relationship between low values of central venous oxygen saturation and anastomotic leak of gastrointestinal sutures in the postoperative period in abdominal trauma surgery. Methods: A cross-sectional prospective study was performed. Patients over 14 years old who required surgical gastrointestinal repair secondary to abdominal trauma were included. Anastomotic leak diagnosis was confirmed through clinical manifestations and diagnostic images or secondary surgery when needed. Central venous oxygen blood saturation was measured at the beginning of surgery through a central catheter. Demographic data, trauma mechanism, anatomic site of trauma, hemoglobin levels, abdominal trauma index, and comorbidities were assessed as secondary variables. Results: Patients who developed anastomotic leak showed lower mean central venous oxygen saturation levels (60.0% ± 2.94%) than those who did not (69.89% ± 7.21%) (p = 0.010). Conclusions: Central venous oxygen saturation <65% was associated with the development of gastrointestinal leak during postoperative time of patients who underwent surgery secondary to abdominal trauma. © 2017 The Author(s).